Influence of graphite particle size on electrical properties of modified PZT-polymer composites - Gobwute Rujijanagul (2018)
Piezoceramics-polymer composites using modified lead zirconate titanate (Pb0.88Sr0.12Zr0.54Ti0.44Sb0.02O3) and polyethylene (PE) were prepared by a calendaring method. The modified ceramic powder was prepared by a conventional solid-state method. Graphite powder of various particle sizes was also added into the composites. Properties of the composites as a function of particle sizes of the ceramics and graphite were studied. The relative permittivity and piezoelectric coefficient (d33) of the composites were found to increase with increasing the particle size of the modified ceramics. Composites contained finer graphite particle also found to give higher d33values. © 2007 Elsevier B.V. All rights reserved.